Plan social media para promover la identidad digital de la cámara de turismo de El Oro. - Chamaidan Carreño, Angie Estefania (Machala, 2021)
This research work is based on the development of a proposal for a communication plan for the social networks of the "Cámara de Turismo de El Oro", where various strategies are proposed that can be implemented in the long term on the fan page of the social network Facebook and Instagram account, in order to promote the digital identity of the organization. For the realization of this project several techniques and research methods were applied, where interviews were conducted with experts in the area of digital communication, marketing and management of social networks of institutions and companies; in order to identify the necessary guidelines to develop the action plan effectively; Likewise, the President and the Executive Director were interviewed as main members of the Board of Directors of the Guild and it was necessary to interview one of the former presidents who was from the beginning of its creation to learn about the history, mission, vision and raison for being of the institution; in order to analyze the organizational situation of Captur El Oro and propose a plan that is in accordance with the institutional guidelines of the guild. Through the observation technique, the current state of the social networks was analyzed, where the level of interaction, reach and number of followers was identified in order to identify the causes of the problem and provide a strategic solution through the proposal of the social media plan; which was finally presented to the Executive Director who is responsible for managing and advising the board of members of Captur El Oro; for its proper functioning; at the end of the presentation he took into consideration the recommendations issued in the document showing interest in implementing the strategies described for the proper management of social networks Facebook and Instagram of the Provincial Chamber of Tourism of El Oro. Since the advent of the internet, the way we communicate has changed; as a result of this, social networks emerged, giving as a result the opportunity to interact with people from all over the world, in the same way the various tools they have allow us to be consumers of content and at the same time creators; making technology part of a basic service of human beings in everyday life; for this reason companies and institutions must be where their target audience is, capture their attention, innovate, reinvent themselves through their publications issued in their social networks in order to enhance their brand. At the institutional level, as is the case of Captur El Oro, this tries to show the various activities carried out to strengthen the tourism sector; one of them is to position the province as one of the most desired destinations showing the benefits it has; using social networks as a tool to help promote these sectors and build trust, credibility, being a respectable institution. In such a way that this project took as a reference the objectives of the guild in order to propose a plan that is aligned to the fulfillment of these objectives.
El presente trabajo de investigación esta basado en la elaboración de una propuesta de plan de comunicación para las redes sociales de la “Cámara de Turismo de El Oro”; en donde se plantean diversas estrategias que pueden ser ejecutadas a largo plazo en la fan Page de la red social Facebook y en su cuenta de Instagram con el objetivo de promover la identidad digital que tiene la entidad gremial. Para la realización de este proyecto se aplicaron varias técnicas y métodos de investigación en donde se hicieron entrevistas a expertos en el área de comunicación digital, marketing y manejo de redes sociales de instituciones y empresas; con la finalidad de identificar las pautas necesarias para poder desarrollar el plan de acción de manera eficaz; así mismo se entrevisto a la Presidenta, al Director Ejecutivo como miembros principales de la Directiva del Gremio y se vio la necesidad de entrevistar a uno de los ex presidentes que estuvo desde el inicio de su creación ; para conocer sobre la historia, la misión, visión y razón de ser de la institución de esta manera poder analizar la situación organizacional de la Captur El Oro y proponer un plan que vaya de acorde a los lineamientos institucionales del gremio. Mediante la técnica de observación se analizó el estado actual de las redes sociales en donde se identificó el nivel que tienen en cuanto a la interacción, alcance y número de seguidores para así identificar las causas del problema y dar una estratégica solución mediante la propuesta del plan social media; que finalmente fue presentado al Director Ejecutivo quién es el encargado de administrar y asesorar a la junta de miembros de la Captur El Oro; para su correcto funcionamiento; al final de la exposición tomo en consideración las recomendaciones emitidas en dicho documento mostrando interés en aplicar las estrategias descritas para el correcto manejo de las redes sociales de Facebook e Instagram de la Cámara Provincial de Turismo de El Oro. Desde la aparición del internet la manera de comunicarnos cambio; fruto de ello surgieron las redes sociales dando como resultado la oportunidad de interactuar con personas de todas partes del mundo, de igual manera las diversas herramientas que poseen nos permiten ser consumidores de contenido y a la vez creadores; volviendo a la tecnología parte de un servicio básico del ser humano dentro de la vida cotidiana; por tal razón las empresas e instituciones deben estar donde se encuentra su público meta, captar su atención, innovar, reinventarse mediante sus publicaciones emitidas en sus redes sociales con la finalidad de potenciar su marca. En el ámbito institucional como es el caso de la Captur El Oro esta trata de mostrar las diversas actividades que realiza para el fortalecimiento del sector turístico; una de ellas es posesionar a la provincia como uno de los destinos más deseado mostrando las bondades que tiene esta; utilizando las redes sociales como una herramienta que ayude a promocionar dichos sectores y generar confianza, credibilidad, siendo una institución respetable. De tal forma que este proyecto tomó como referencia los objetivos del gremio para poder proponer un plan que este alineado al cumplimiento de estos.
Keywords: IDENTIDAD DIGITAL; RED SOCIAL; SOCIAL MEDIA; COMUNICACION DIGITAL